2015
DOI: 10.1159/000368766
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Proton Pump Inhibitor-Resistant Nonerosive Reflux Disease by Esophageal Manometry and 24-Hour Esophageal Impedance and pH Monitoring

Abstract: Background: Patients with proton pump inhibitor (PPI)-resistant nonerosive reflux disease (NERD) include subgroups that have markedly different pathophysiology. This study aimed to clarify the pathophysiology of NERD by esophageal manometry with 24-hour esophageal impedance and pH monitoring. Methods: Eighteen consecutive outpatients referred to our expert center for functional gastrointestinal motility with suspected PPI-resistant NERD were enrolled. Manometry was performed to detect esophageal motility disor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 21 publications
2
14
0
Order By: Relevance
“…In Japan, persistent symptoms despite taking standard doses of PPI were regarded as PPI-resistant NERD in some reports [5,6], and those despite taking double doses of PPI were regarded as PPI-resistant NERD in others [17,18], but the latter are defined as PPI-resistant NERD in many reports from Western countries [13,15,19,20,21]. To rule out acid reflux as much as possible, taking a double dose of PPI should be tried once, and we defined these patients with persistent symptoms as PPI-resistant NERD.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In Japan, persistent symptoms despite taking standard doses of PPI were regarded as PPI-resistant NERD in some reports [5,6], and those despite taking double doses of PPI were regarded as PPI-resistant NERD in others [17,18], but the latter are defined as PPI-resistant NERD in many reports from Western countries [13,15,19,20,21]. To rule out acid reflux as much as possible, taking a double dose of PPI should be tried once, and we defined these patients with persistent symptoms as PPI-resistant NERD.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we do not include IEM in primary esophageal motility disorder as a cause of NERD. In previous reports on esophageal motility disorder as the cause of PPI-resistant NERD, Kawamura et al [5] reported that primary esophageal motility disorder was noted in 5 (28%) of 18 PPI-resistant NERD patients, 1 had achalasia, 1 had nutcracker esophagus, and 3 had diffuse esophageal spasm. They noted IEM in 3 patients, but it was not included as the cause of persistent symptoms, and we also did not include it.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kawamura et al [10] performed HRM in 18 PPI-resistant NERD patients with persistent symptoms despite standard-dose PPI therapy for 8 weeks, in which NERD was defined as troublesome reflux-associated symptoms in the absence of mucosal breaks on endoscopy. In this study, approximately one-third of consecutive patients referred with suspected PPI-resistant NERD [11,12,13,14,15,16,17] had primary esophageal motility disorders.…”
Section: Discussionmentioning
confidence: 99%
“…5 Other causes for PPI resistance or failure can be due to esophageal dysmotility disorder, paraesophageal hernia, and erosive esophagitis. 6,7 Laparoscopic Nissen fundoplication (LNF) is the gold standard treatment for medically refractory GERD. Although the LNF provides excellent resolution of GERD, the extensive operative procedural manipulation may…”
Section: Introductionmentioning
confidence: 99%